2015
DOI: 10.1002/cbdv.201500060
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Supplementation Prevents Selenite‐Induced Cataractogenesis in Sprague Dawley Rat Pups

Abstract: Luteolin, a flavonoid present in leaves and stems of many plants finds mention in literature for beneficial effects on eyes. Presently, no reports are available on the in vivo anticataractogenic effect of luteolin. The current study was designed to evaluate the efficacy of luteolin on selenite-induced cataract models in vivo. The study consisted of three groups of Sprague Dawley rat pups 8-10 d old (Group I (Normal), Group II (Cataract induced), and Group III (Treatment)). Cataract was induced in Group II and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Luteolin lowers the oxidative damage and enhances the antioxidant potential induced by cataracts of rat lens in selenite. Membrane integrity of the rat lens was also improved by luteolin (Sreelakshmi, Sasikala, & Abraham, ). Disease like multiple sclerosis causes nerve damage, affects the immune system, fatigue, and causes pain.…”
Section: Pharmacological Activities Of Luteolinmentioning
confidence: 99%
“…Luteolin lowers the oxidative damage and enhances the antioxidant potential induced by cataracts of rat lens in selenite. Membrane integrity of the rat lens was also improved by luteolin (Sreelakshmi, Sasikala, & Abraham, ). Disease like multiple sclerosis causes nerve damage, affects the immune system, fatigue, and causes pain.…”
Section: Pharmacological Activities Of Luteolinmentioning
confidence: 99%
“…In injured cells, this mechanism needs an overexpression of UCP‐2, so flavones may contribute to their ability in reducing ROS production from mitochondria in affected or injured cells, as with lenses in cataract . This suggestion may explain why treated rats increased their caspase‐3 activity and calcium level in eye lenses of crystalline .…”
mentioning
confidence: 93%
“…The authors of the commented paper reported that Sprague–Dawley rat pups, at 8 – 10 days age post‐partum, when treated with a dose as low as 1.0 μg/g luteolin (Group III), restored a phenotype comparable to wild type (Group I) . Luteolin‐nontreated group, with induced cataract (Group II), suffered from higher oxidative stress and ROS production, an increase in caspase‐3 activity in lenses associated with an increase in calcium level and a reduction in the activity of [Ca 2+ ]ATPase . In the past, toxic metabolites derived from oxygen reactive radicals and peroxides, have been related to the onset of cataract and quite recently with mitochondria activity in the lens .…”
mentioning
confidence: 99%
See 2 more Smart Citations